On deficits and symmetries in a fiscal capacity - Shafik Hebous; Alfons J. Weichenrieder (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
There is a growing debate about complementing the European Monetary Union by a more comprehensive fiscal union. Against this background, this paper emphasizes that there is a trade-off in designing a system of fiscal transfers ("fiscal capacity") in a union between members of different size. A system cannot guarantee symmetric treatment of members and simultaneously ensure a balanced budget. We compute hypothetical transfers for the Eurozone members from 2001 to 2012 to illustrate this trade-off. Interestingly, a symmetric system that treats shocks in small and large countries symmetrically would have produced large budgetary surpluses in 2009, the worst year of the financial crisis.
urn:nbn:de:hebis:30:3-385870
Keywords: H50; H60; 330; fiscal union; asymmetric shocks; federal transfers; optimum currency area